Phase 2, randomized, double‐blind study of pracinostat in combination with azacitidine in patients with untreated, higher‐risk myelodysplastic syndromes. Issue 6 (17th January 2017) - Garcia‐Manero, Guillermo; Montalban‐Bravo, Guillermo; Berdeja, Jesus G.; Abaza, Yasmin; Jabbour, Elias; Essell, James; Lyons, Roger M.; Ravandi, Farhad; Maris, Michael; Heller, Brian; DeZern, Amy E.; Babu, Sunil; et al.
Abstract : BACKGROUND: The prognosis of patients with higher‐risk myelodysplastic syndromes (MDS) remains poor despite available therapies. Histone deacetylase inhibitors have demonstrated activity in patients with MDS and in vitro synergy with azacitidine. METHODS: A phase 2 randomized, placebo‐controlled clinical trial of azacitidine and pracinostat was conducted in patients who had International Prognostic Scoring System intermediate‐2–risk or high‐risk MDS. The primary endpoint was the complete response (CR) rate by cycle 6 of therapy. RESULTS: Of 102 randomized patients, there were 51 in the pracinostat group and 51 in the placebo group. The median age was 69 years. The CR rate by cycle 6 of therapy was 18% and 33% ( P = .07) in the pracinostat and placebo groups, respectively. No significant differences in overall survival (median, 16 vs 19 months, respectively; hazard ratio, 1.21; 95% confidence interval, 0.66‐2.23) or progression‐free survival (11 vs 9 months, respectively; hazard ratio, 0.82; 95% confidence interval, 0.546‐1.46) were observed between groups. Grade ≥3 adverse events occurred more frequently in the pracinostat group (98% vs 74%), leading to more treatment discontinuations (20% vs 10%). CONCLUSIONS: The combination of azacitidine with pracinostat did not improve outcomes in patients with higher‐risk MDS. Higher rates of treatment discontinuation may partially explain these results, suggesting alternative dosing and schedules to improve tolerability may be required to determine the potential of the combination. Cancer 2017;123:994–1002. © 2016 American Cancer Society . Abstract : The combination of azacitidine with pracinostat does not improve outcomes in patients with higher‐risk myelodysplastic syndromes. Higher rates of treatment discontinuation may partially explain these results. See also pages 911‐4.